PENGGUNAAN PESTISIDA DAN KADAR CHOLINESTRASE PADA PETANI PENYEMPROT - Girsang, Vierto Irennius; Barus , Apriani Novaria; Hutajulu, Johansen; Siregar, Laura Mariati (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
Using pesticides can decrease the population of organisms in plants. A pesticide which the work of cholinesterase enzyme in the body is oregano phosphate; it also has a side effect on the decrease in cholinesterase content. The research used a cross-sectional design which was aimed to find out the influence of using pesticides on the decrease in blood cholinesterase content in farmers who spray their plants with pesticides at Desa Cikaok, Kecamatan Sitellu Talli Urang Julu, Kabupaten Pakpak Bharat. The samples were farmers who sprayed their plants with pesticides. Chi Square statistic test was used to find out the variables which probably decrease in cholinesterase content at p,0,05. It was found that 26,7% of the respondents underwent a normal decrease in cholinesterase content, and 73,3% of the respondents underwent an abnormal decrease. Statistically, there was a significant correlation between the length of spraying pesticides with the decrease in cholinesterase content in the blood of farmers who sprayed their plants with pesticides at Desa Cikaok at p-value = 0,678. It is recommended that the farmers lessen the duration of spraying in order to reduce the risk of exposure to pesticides and use personal protective devices such as gloves, hats masks, glasses, uniforms, and shoes. The regional government should provide protection, counseling, and training about the procedure of using pesticides in order to forestall the incidence of illness in the farmers who sprayed their plants with pesticides.